CREACIÓN DE VIVEROS DE LA PLANTA STEVIA CON CUIDADOS TÉCNICOS Y DISTRIBUCIÓN POR VARIAS VÍAS - Miranda Burgos, Mercedes Alexandra (2019)
In recent years, entrepreneurship has been forging a high level of importance and positive impact in all nations, since entrepreneurship has become a global strategy to address the constant economic problems that societies coexist with in the current century. It is worth mentioning that different entrepreneurial proposals have emerged in the gastronomic field, in the textile field, in the ecological field (focused on the use of recyclable materials to generate new products), and in the agricultural field where adaptation has been sought. of new crops of plants with nutritional and medicinal properties in different countries for subsequent internal consumption and also export of products and derivatives to international markets.